Peran Literasi Budaya dan Kewargaan dalam Upaya Pelestarian Kebudayaan Lokal Nusantara di Era Revolusi Industri 4.0 - Ervina Anatasya; Dinie Anggraeni Dewi; Rizky Saeful Hayat (LPPM Politeknik Pratama, 2024)
The development of globalization is increasingly having an impact on the existence of local culture in the archipelago. The era of globalization and increasingly rapid technology has made Indonesian people more interested in foreign culture. Using the literature method, this article was created to discuss the role of cultural literacy and citizenship in maintaining Indonesian culture in modern realities in the era of globalization. Efforts that can be made are to implement cultural and civic literacy in schools and the general public (digitally). Traditional Indonesian culture and values must continue to be maintained and preserved because they are part of the identity of the Indonesian nation.